Feasibility of double-layer microchannel fabrication at low speed micro end-mill and wire-cut EDM machines - Seder, Islam M.F.; Ahmed, Mirghani Ishag; Ahmed, Shugata; Hawlader, M.N.A. (AENSI Journals, 2014)
This study compares micron-scale features of double layer-microchannel heat sink (DLMC) fabrication.Massive theoretical researches investigated DL-MC and its advantages over single-layer. However, micro-machining of DL-MC is still immature area. Here,Two advanced machining technologies, namely: Micro end-mill and wire-cut EDM are utilized to fabricate a DL-MC. Investigation on burr formation, surface roughness and shape configuration that influence heat transfer mechanism is done through a series of machining runs. Manipulating machine parameters such as: spindle speed, feed rate and tool dimension shown that low speed micro end-mill is capable of creating sufficient DL-MC quality. Also, scanning electron microscope (SEM) micrographs and roughness measurement reveal that wire-cutEDM is better in machining time and stability of surface roughness.